Bio-inspired structures : Structures with light weight and good energy absorption - Kankainen, Antti (My University, 2025)
Nature has long served as an inspiration for engineering and material design, leading to the development of bio-inspired structures that combine lightweight properties with high energy absorption. These structures are particularly relevant in applications requiring impact resistance, structural efficiency, energy efficiency, and material savings. Given the challenges posed by climate change and the finite nature of natural resources, studying these characteristics is increasingly important. This thesis explores bio-inspired structures, focusing on their mechanical properties and potential for real-world applications. This thesis begins with an overview of various bio-inspired structural concepts, highlighting their origins in biological systems. The focus is on bio-inspired cellular structures and plates. These structures exhibit superior mechanical performance due to their optimized geometry and hierarchical organization. Key properties such as stiffness, strength-to-weight ratio, and energy absorption capabilities are discussed in relation to their natural counterparts. A specific emphasis is placed on honeycomb structures, which are widely recognized for their strength and efficiency. Two research articles are analysed to provide deeper insights into the mechanical behaviour and optimization of honeycomb-inspired designs. These studies illustrate how material selection, unit cell geometry, and structural modifications influence energy dissipation and overall mechanical performance. The findings suggest that bio-inspired designs provide significant advantages in aerospace, automotive, and protective equipment applications, where weight reduction and impact resistance are critical. Leveraging insights from biological models enables engineers to develop more efficient and sustainable materials that enhance performance while minimizing resource consumption. This thesis contributes to bio-inspired engineering research by demonstrating how natural design principles enhance structural optimization. Future research could explore advanced manufacturing techniques, such as additive manufacturing, to further refine and expand the applicability of these structures.
Keywords: Bio-inspired structures, energy absorption, strength-to-weight ratio